Professionalism and Pesticides: Supervision - Frederick M. Fishel (EDIS, 2009)
PI-176, a 2-page illustrated fact sheet by F. M. Fishel, describes the extent of supervision required by law in Florida for various types of licenses and pesticide label restrictions. Includes additional sources of information. Published by the UF Department of Agronomy, January 2009.